Caring for our children : national health and safety performance standards, guidelines for early care, and education programs. (APHA Press, imprint of American Public Health Association ; American Academy of Pediatrics ; National Resource Center for Health and Safety in Child Care and Early Education, 2019)
The fourth edition contains guidelines on the development and evaluation of the health and safety of children in early care and education settings. This guide features 10 chapters of more than 650 standards and dozens of appendixes with valuable supplemental information, forms, and tools. --